EMPOWERING EFL STUDENTS THROUGH ARGUMENTATIVE WRITING: A PATH TO CRITICAL LITERACY IN ENGLISH EDUCATION - Aisyah, Siti; Putri, Icha Syafira Rizqi Arsy (STKIP Persada Khatulistiwa Sintang, 2025)
Abstract: In many EFL classrooms, students struggle to express complex ideas in English beyond basic conversation. This paper argues that argumentative writing can serve as a strategic bridge between language development and critical engagement. Drawing from descriptive classroom analysis and practical teaching experience, the study explores how writing structured arguments supports learners in constructing logical reasoning, defending perspectives, and interacting with diverse viewpoints. Through consistent practice, students not only build linguistic fluency but also develop habits of reflection and independent thought. The study highlights that integrating argumentative writing into EFL instruction enhances learners’ academic readiness and critical literacy. Implications for teaching practice and curriculum development are discussed based on field observations and theoretical grounding.Keywords: argumentative writing; EFL learners; critical thinking; literacy development; classroom practice